Reuse of Microsuture Material - Dr. Dilipkumar Gahankari; Dr. Madhavi Godghate; Dr. Nimmi Lalwani (Indian Journal of Plastic Surgery)
Described here is simple technique of reusing micropoint needles and left over broken pieces of 8-0 and 10-0 monofilament nylon.